The Study of Slang by Nicki Minaj in Pink Friday Album - Kadek Indah Wulanningtyas Tyas (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2021)
The study concerns with the slang words in song lyrics in Nicky Minaj Album. The aims of the study are (1) to analyze the types of the slangs in the lyrics, and (2) to analyze the slang word formations. The method of the research was descriptive qualitative. The data were obtained through listening to the songs and reading the song lyrics. From all of the collected data only 6 samples have been analyzed. The method of the study was descriptive qualitative. The writer used theory types of slang in the lyrics by using the theory by Chapman (2007), and theory slang word formations by using the theory by Mattiello (2008) to answer the questions. Based on the theory, there are two types of slang, namely primary and secondary slangs. There are two types of slang, namely primary and secondary slangs. There were 2 words that were identified as primary slangs: crusty, niggas and legit. This research found 5 secondary slangs, e.g.man, fuck, ‘bout, wanna, and baby. The types of word formations used for creating the slang words are 5, namely compounding, acronyms and initialisms, blending, clipping, and word manufacture and fanciful formations. There were 2 compounding,1 acronyms and initialisms, 1 blending, 3 clipping, and 1 word manufacture and fanciful formations.